2018
DOI: 10.22616/erdev2018.17.n192
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of main parameters of tractor and unit for seeding cereal crops with regards to their impact on crop productivity

Abstract: Abstract. The article determines the weight and power of the tractor, as well as the width of the seeder and the operational speed of the tractor-seeder unit based on the new method. Using multi-cycle, multi-parameter calculations, it is revealed that the seeding operation quality could be achieved with a single combination of optimal values of the tractor weight and power, which are almost the same even within different environmental conditions. The main influence on the optimal value of the tractor weight an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…The article proposes to use an objective, integrated criteriontotal energy costs [17] as a criterion for optimizing the MTFs composition and the parameters of a machine and tractor unit in a technological operation. [18][19][20]. The model allows for various optimization calculations, including the identification of the optimal annual tractor load for various technological operations, taking into account the stress of environmental factors and tractor parameters on the formed crop yield.…”
Section: Methodsmentioning
confidence: 99%
“…The article proposes to use an objective, integrated criteriontotal energy costs [17] as a criterion for optimizing the MTFs composition and the parameters of a machine and tractor unit in a technological operation. [18][19][20]. The model allows for various optimization calculations, including the identification of the optimal annual tractor load for various technological operations, taking into account the stress of environmental factors and tractor parameters on the formed crop yield.…”
Section: Methodsmentioning
confidence: 99%
“…Research into new high-efficiency technical solutions for the production and processing of seeds of different crops will be initiated for many years, both in Russia [1][2][3][4][5] and in various countries of America [6] and Eurasia [7][8][9]. When processing sunflower seeds, one of the important technological operations that determine the quality of the products obtained is peeling -separation of the outer bran of the seed from the core.…”
Section: Introductionmentioning
confidence: 99%
“…Leading scientists from many countries are engaged in the development and improvement of tillage machines with rotary working tools [2][3][4][5][6]. Having studied the research in this area, we revealed that the use of rotary working tools is a promising direction in the development of new machines for tillage [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%